THE EFFORTS TO INCREASE STUDENTS' SELF-CONFIDENCE THROUGH OUTBOUND METHOD IN CORNER LEARNING THEME 1 GAMES AND SPORTS CLASS III: EFFORTS TO INCREASE STUDENTS' SELF-CONFIDENCE THROUGH OUTBOUND METHOD - Iskandar, Aris; Pontoh, Sholeha; Damopolii, Mujahid (STIT Pringsewu, 2024)
This research aims to determine whether the outbound method can increase students' self-confidence in learning Physical Education, Sports and Health (PJOK) Theme 1 Games and Sports Class III at SDN 4 Limboto. The outbound method is expected to increase students' self-confidence. The research model is classroom action research by Kemmis Mc Tagart. The research subjects were 22 class III students at SDN 4 Limoboto. Data collection techniques were carried out by means of observation, interviews and documentation. The research design has four models, namely: observation, planning, action and reflection. The research results show that outbound activities can increase the self-confidence of class III students at SDN 4 Limboto, which can be seen from the percentages obtained. During the pre-cycle the average percentage was 43.59% before action was taken, then after action was taken in cycle I the average percentage value increased to 68.48%, and increased again in cycle II with an average percentage value of 87. 93% and has achieved a success rate of 75%. Therefore, outbound activities can increase the self-confidence of class III students at SDN 4 Limboto.